Penerapan Model Waterfall dalam Pengembangan Sistem Informasi Akademik Berbasis Web sebagai Sistem Pengolahan Nilai Siswa - Kevin Fahrezi; Ahmad Rifqi Mulana; Sandra Melinda; Nurhaliza Nurhaliza; Sri Mulyati (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
In a school, teachers have difficulty managing student grades because they still use the manual method. The development carried out has the aim of creating a value management information system that will make it easier for teachers to manage student grades, because teachers need to handle student scoring activities which require a lot of time and require considerable accuracy. This information system will be applicable at the Vocational High School (SMK) level. This system is web-based, so that teachers can access the web for value management and students can also access the web to see the results of their learning. The development method applied to this development is by using the waterfall method. The results of this development are to facilitate and accelerate the performance of teachers in managing student grades in the school and become a benchmark for students so that students can understand their learning outcomes.